PERANAN KELUARGA DALAM PENDIDIKAN KARAKTER ANAK - Ermidawati Ermidawati (JURNAL KELUARGA SEHAT SEJAHTERA, 2013)
ABSTRACT Family is one of the important factors for the success of children's education, especially educating children  with  religious values. Families have  responsibilities  to pay attention to the mental development of the child as a whole family education is a process of transformation in the behavior and attitude of the group or the smallest social unit in society. Because the family is the first and foremost cultural environment is in instilling norms and develop habits and behaviors that are important for personal life, family and community. Key to the success of education in the family lies in the spiritual education to someone religious meaning.   Faith, morals,  knowlge  and   creativity.play an important role in shaping one's view of life. One consequence is, that in giving attention to the physical development of children, with consideration shall ensure non-physical development of children. In providing   meals, the children must be given good food, not just from the point of health, but also from the point of Shari'ah. The food was good from the health point of view will help the growth and development of children in the areas of physical, whereas halal food needed to ensure the development of personality and soul. Character education in the family is the process of transformation in the behavior and attitude of the group or the smallest social unit in society. Because the family is is the first and foremost cultural environment in instilling norms and developed various habits and behaviors that are important for personal life, family and community.  Kata Kunci : Pendidikan karakter dan keluarga.